Maintenance and Management in Engineering - Hesham Almomani, Abdulaziz Abdullah Almutairi (International Journal of Advanced Science and Technology, 2020)
Introduction: Since the industrial revolution, protection of engineering system inside the discipline has been a mission. Even though dazzling development has been made in retaining equipment within the area in an effective way, maintenance of system is still an undertaking due to factors together with size, cost, complexity, and competition. For this reason, there's an exact need for powerful asset management and preservation practices a good way to definitely affect important achievement elements together with protection, product fine, speed of innovation, price, profitability, and dependable delivery.